Integrating Nearpod into Digital Learning to Enhance Students’ Confidence in Expressing Opinions - Sofia; Novita Sari; Supriadi Torro (Universitas Negeri Yogyakarta, 2026)
Active student involvement is a fundamental component for establishing successful teaching and learning processes in higher education. Nevertheless, a significant number of university students still exhibit passive behavior during classroom discussions, primarily because they lack the confidence needed to voice their ideas. The use of interactive digital platforms presents a viable alternative to foster a learning atmosphere that is more engaging and participatory. The objective of this research is to evaluate how interactive digital learning via Nearpod affects university students' confidence levels when expressing their academic opinions. A quantitative methodology was utilized, specifically implementing a quasi-experimental approach with a pretest-posttest control group design. The participants comprised students taking the Classroom Action Research course within the Sociology Education Study Program at Universitas Negeri Makassar. Information was gathered utilizing a Likert-scale questionnaire measuring self-confidence, and the results were evaluated using N-Gain, independent sample t-tests, and effect size calculations. The findings demonstrate that the group utilizing Nearpod exhibited a more substantial growth in self-confidence than the traditional control group. Specifically, the experimental group achieved a moderate N-Gain score of 0.63, whereas the control group only reached a low score of 0.19. Furthermore, statistical evaluations indicated a meaningful variance between the two groups (p < 0.05), accompanied by a large effect size of 0.87. These results imply that Nearpod's interactive tools—especially the voice response function—serve as a secure digital space that supports students in progressively developing their courage to communicate academic thoughts.